2016
DOI: 10.1159/000445283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Antihypertensive Drugs on the Cerebral, Renal and Splanchnic Tissue Oxygen Extraction of Preterm Neonates

Abstract: Background: Drugs with antihypertensive action are frequently used in obstetrics for the treatment of preeclampsia (labetalol) and tocolysis (nifedipine) or for neuroprotection (MgSO4), and may affect the hemodynamics of preterm born neonates. Objective: The aim of this study was to assess whether maternal antihypertensive drugs affect multisite oxygenation levels of the neonate. Methods: Eighty preterm neonates of ≤32 weeks of gestational age were monitored using near-infrared spectroscopy. Mean ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
15
1
1
Order By: Relevance
“…Both the splanchnic perfusion and its reproducibility in the mesenteric territory in preterm infants using NIRS have been extensively studied [12,17,20,21,22,23,24,25,26]. Petrova et al [27] did not find significant differences in cerebral, mesenteric, or renal rSO 2 in a cohort of preterm infants <32 weeks gestation with PDA with a diameter ≥3 versus <3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Both the splanchnic perfusion and its reproducibility in the mesenteric territory in preterm infants using NIRS have been extensively studied [12,17,20,21,22,23,24,25,26]. Petrova et al [27] did not find significant differences in cerebral, mesenteric, or renal rSO 2 in a cohort of preterm infants <32 weeks gestation with PDA with a diameter ≥3 versus <3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of evidence, and conflicting results about the effect of antenatal MgSO 4 on both cerebral oxygenation and the incidence of severe IVH, and the reports suggest that outcomes may depend on the antenatal maternal magnesium dose/serum concentrations and neonatal serum magnesium concentrations. [21][22][23][24][25][26][27][28] Despite the uncertainty about the exact mechanism of fetal MgSO 4 neuroprotection, some factors have been asserted to have a role in lowering CP risk. MgSO 4 was shown to have multiple direct effects on the nervous tissue, such as blockade of NMDA (N-Methyl-d-aspartate) receptors and increasing angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…21 There are two other studies both searching for the effect of maternal antihypertensive drugs, including MgSO 4 as it has blood pressure lowering properties, on the cFTOE in the preterm infants during the first day after birth. 22,23 Both found a lowered cFTOE in infants with antenatal MgSO 4 exposure. However, both studies were unable to entangle whether this effect resulted from underlying disease such as preeclampsia or concomitantly given labetalol.…”
mentioning
confidence: 96%
“…We previously reported that antenatal MgSO 4 is associated with a lower neonatal cerebral fractional tissue oxygen extraction (cFTOE), either due to reduced cerebral oxygen consumption associated with lower cerebral metabolism or increased cerebral oxygen supply through vasodilatory mechanisms [6]. Although MgSO 4 has been reported to affect cerebral blood flow (CBF), a confounding effect of maternal PE can frequently not be excluded [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although MgSO 4 has been reported to affect cerebral blood flow (CBF), a confounding effect of maternal PE can frequently not be excluded [7][8][9]. Likewise, fetal brain sparing (preferential cerebral perfusion in response to placental insufficiency) may have influenced these findings [6,10].…”
Section: Introductionmentioning
confidence: 99%